What Does a Cardio-oncology Service Offer to the Oncologist and the Haematologist?. Issue 8 (August 2021) - Andres, M.S.; Pan, J.; Lyon, A.R.
Abstract: Cardio-oncology is an emerging subspecialty arising from the need for multidisciplinary collaboration to address the increasing prominence of cardiovascular disease (CVD) among cancer patients. This overview outlines the case for establishing cardio-oncology services and defines the ways in which these services benefit cancer patients. The primary objective of cardio-oncology is to manage CVDs in order to allow cancer patients to complete the best cancer treatments safely and with minimal interruption. In the decades since the first discovery of heart failure induced by anthracycline chemotherapy, both cardiovascular and oncological science have advanced considerably. Cardio-oncology services aim to bring together expertise from these two fast moving fields in order to provide optimal evidence-based care for cancer patients with CVDs. Here we discuss the basis of cardio-oncology services by presenting their rationale and key components, as well as their essential roles in education, training and research. At each stage of the cancer care pathway, a cardio-oncology service can add value by ensuring cancer patients have timely access to specialist care backed up by cutting edge diagnostic tools and treatment options, as well as holistic supports. We highlight areas of recent and upcoming developments in the field that are likely to change established clinical practice. Improved cardiac imaging modalities can detect chemotherapy-related cardiac dysfunction earlier and are also essential for the prompt diagnosis of an expanding range of cardiovascular effects complicating newer cancer therapeutics, such as immune checkpoint inhibitors and other targeted therapies. Modern cancer therapy has dramatically improved cancer survival and as such CVD is becoming one of the principal determinants of overall outcome for cancer patients. A dedicated cardio-oncology service can facilitate the optimisation of cardiovascular treatment and enable the completion of cancer therapy. A multidisciplinary collaborative approach is key to achieving these objectives.